Accelerated carbonation by cement kiln dust in aqueous slurries: chemical and mineralogical investigation. Issue 4 (26th April 2017) - Medas, Daniela; Cappai, Giovanna; De Giudici, Giovanni; Piredda, Martina; Podda, Simona
Abstract: Cement kiln dust accelerated carbonation in aqueous slurries at 25°C and 3 bar PCO2 was investigated by X‐ray diffraction analysis, solution chemistry, scanning electron microscopy, and energy dispersive spectroscopy to better understand chemical and mineralogical processes governing CO2 uptake. Dissolution of lime, portlandite, and ettringite occurs primarily in the carbonation process. These provide Ca 2+ ions to react with CO3 2− ions leading to calcite bulk precipitation from solution. Concomitantly, the dissolution of Ca‐(Al)‐silicate grains takes place but it is limited by the formation of a Si‐rich and Ca‐depleted rim which appears onto the grain surfaces due to an initial hydration step. The Si‐rich decalcified rim hinders the diffusion of Ca 2+ ions from the core of silicate grains to the bulk solution. The diffusion of Ca ions through the rim is then the rate limiting step for the carbonation of Ca‐(Al)‐silicate, that accounts for up to 4% of the carbonation potential. Achieved results elucidate the processes governing CO2 uptake by cement kiln dust, and are fundamental in the perspective of enhanced CO2 sequestration by cement kiln dust. © 2017 Society of Chemical Industry and John Wiley & Sons, Ltd.